HOW TO PROMOTE TEXT COMPREHENSION WITH PUPILS OF GRADES 1–6 WHEN TEACHING TO SOLVE COMBINATORIAL PROBLEMS - Krastiņa, Elfrīda; Sondore, Anita; Drelinga, Elga (Acta Paedagogica Vilnensia, 2015)
It is essential to train pupils in working with diverse information resources and making use of various strategies for solving mathematical problems. To determine the probability of various events, knowledge of the strategies for solving combinatorial problems as well as adequate reading competence are essential.Research problem– how to promote text comprehension of pupils of Grades 1–6 when teaching to solve combinatorial problems in the Latvia. Research questions – Which mathematical problems are difficult for pupils in national diagnostic tests in Grades 3 and 6? What is the teachers’ opinion about pupils’ ability to solve mathematical word problems (focus on pupils in Grades 1 to 6)? What is the teachers’ opinion about the use of strategies for solving problems with elements of combinatorics?To answer the research questions, an evaluative case study design was created. The authors conducted analysis of relevant educational documents, performed content analysis of combinatorial problems which pupils in Grades 1–6 have to master, carried out a survey of 130 primary school teachers, analyzed the results of national diagnostic tests of Grade 3 and Grade 6 (2014–2015) in mathematics and in the Latvian language and performed observation of problem solving strategies used in primary school.This paper examines some typical primary school pupils’ difficulties in solving combinatorial problems. Suggestions are proposed for drafting relevant methodological recommendations for teachers for teaching to solve non-standard problems.
Keywords: elements of combinatorics; reading comprehension; problem solving strategies